2015
DOI: 10.1016/j.ecolmodel.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Influences of setting sizes and combination of green infrastructures on community’s stormwater runoff reduction

Abstract: Implementation of green infrastructures is an effective option for mitigating the impacts of increasing urbanization on stormwater runo ff. In this study, we evaluated the runoff reduction effectiveness under various setting sizes of green infrastructures using a process-based stormwater runoff model. The model was validated with field data from a typical community in Beijing and proved to be accurate in estimating stormwater runoff under larger rain events. The pervious area percentage and soil hydraulic prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 40 publications
0
19
0
2
Order By: Relevance
“…When distributed rain gardens at the household level were added to the simulation, little further reductions were observed. Models have also been used to optimize pollutant removal and cost (Liu, Chen & Peng, 2015) and to determine most acceptable areas for siting of SCMs based on biophysical and societal constraints (Lee et al, 2012;Martin-Mikle et al, 2015;Steinman et al, 2015).…”
Section: Cumulative Effects Of Scms On Water Qualitymentioning
confidence: 99%
“…When distributed rain gardens at the household level were added to the simulation, little further reductions were observed. Models have also been used to optimize pollutant removal and cost (Liu, Chen & Peng, 2015) and to determine most acceptable areas for siting of SCMs based on biophysical and societal constraints (Lee et al, 2012;Martin-Mikle et al, 2015;Steinman et al, 2015).…”
Section: Cumulative Effects Of Scms On Water Qualitymentioning
confidence: 99%
“…The presence of nearby impervious surfaces may support the effectiveness of GSI features promoting infiltration. In urbanized centers, impervious surface coverage may vary by block or parcel any change relatively rapidly necessitating the consideration of site-specific conditions [8,[28][29][30][31]. In most cases, the engineering practices underlying GSI features necessitate proximity to a stormwater inlet to manage excess overflow and drainage [29].…”
Section: Siting Green Stormwater Infrastructurementioning
confidence: 99%
“…Owing intensities of LID implementation predicted runoff volume reductions of 25% to 30% for storm events ranging up to 25 mm in magnitude within watersheds ranging from 5 to 9,300 ha (Vittorio and Ahiablame, 2015;Liu, Chen and Peng, 2015;Palla and Gnecco, 2015). However, these hydrologic benefits were shown to diminish with increases in storm magnitude and/or decreases in the relative stormwater control and treatment area.…”
Section: Watershed-scale Lid Assessmentmentioning
confidence: 99%
“…As reviewed by Askarizadeh et al (2015), various spatialbased modeling tools have been developed to identify optimal selection and siting of LID practices to achieve hydrologic and other benefits at the lowest incremental cost. Findings from optimization-type LID studies in 2015 indicated integration of infiltration-based and harvest-based LID practices could provide greater cost-benefits than only one or the other (Askarizadeh et al 2015;Jia, Yao et al, 2015;Liu, Chen and Peng, 2015;Liu, Bralts, and Engel, 2015). Baek et al (2015) proposed a methodology to optimize LID selection for reductions in first flush effects.…”
Section: Watershed-scale Lid Assessmentmentioning
confidence: 99%